Pengaruh Latihan Memukul Ban Menggunakan Palu Terhadap Kekuatan Otot Perut Atlet Judo - Ilmi Nurfitriani; Kusnadar Kusnandar; Arfin Deri Listiandi; Panuwun Joko Nurcahyo; Ayu Rizky Febriani; Bayu Suko Wahono (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2022)
The training method is one way to improve the physical condition of athletes. One of the training methods that can be used to improve the components of physical condition, especially the strength of the abdominal muscles, is the practice of hitting tires using a hammer. The purpose of this study was to determine the effect of hitting tires using a hammer on the strength of the abdominal muscles of judo athletes in Brebes Regency. This research is experimental research with one group pretest posttest design. The number of samples in this study were 15 judo athletes (5 male and 10 female) using total sampling. The instrument used in this study was a sit up test with a test validity of 0.96 and a test reliability of 0.94. Data analysis used the prerequisite test for normality and homogeneity, while the hypothesis test used the Paired Sample t-Test by comparing the pretest and posttest scores in one group. The results showed that there was a significant effect of hitting tires using a hammer on the strength of the abdominal muscles of judo athletes in Brebes Regency with a significance value of 0.000. Conclusion: The practice of hitting tires using a hammer provides an increase in the strength of the abdominal muscles of judo athletes in Brebes Regency. The increase in abdominal muscle strength by 45.98%, so that the exercise of hitting the tires can be applied in an exercise program to increase the strength of the abdominal muscles of judo athletes